Applying Fitts` Law during the jump on gymnastics springboard - Kamenjaševic, E.; Atikovic, A.; Nožinovic Mujanovic, A. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
The aim of this study was to determine another new variable in precision indicators Fitts low during the jump on springboard and placement foot on the springboard. The literature was searched to identify as relevant studies as possible through following the results from World Cup Qualification - men Ljubljana, 2000 (n=28) and World Championship Qualification in Debrecen, 2002 (n=8). For predicting, Fitts' law (is an equation giving the time to acquire and select a target based on the distance moved and the size of the target index of difficulty (ID). As a result; the higher the value of the index, the more difficult the task, and the more time needed to reach the target or gymnastics springboard. On the vault, the judges have to evaluate a single element, so it must be evaluated on the basic of even more deduction factors than routines on the other apparatues. Initial ratings in the vault from a biomechanical point of view can be more objectively determined by the expert of the Men`s and Women`s FIG Technical Committee